La calidad del servicio educativo y de atención de los centros infantiles del Buen Vivir, perspectiva y expectativas de los padres de familia :studio de caso en el CIBV Luis Fernando Ruiz del Cantón Latacunga, Provincia Cotopaxi - Umajinga Pastuña, Maria Martha (2015)
Education and care that children should receive during their early childhood understood it in 0-3 years is a fundamental reason why the government is committed to improving these aspects by creating children's centers of Good Living, as is CIBV the case of Luis Fernando Ruiz. This research aimed to analyze the information collected on the quality of educational services and care offered by this CIBV from the perspective of parents. The quality of service provided by the children's center in relation to education and care was analyzed. As a result of this investigation, aspects that should be improved to achieve quality service and warmth in an environment tailored to the needs of children who attend there were identified.